Spatial mapping for climate resilient agri-food systems in the coastal zone of Bangladesh - Ali, A M M Mostafa; Rahman, Md. Mostafizur; Saha, Champa Rani; Nisha, Nusrath Jahan; Laborte, Alice G.; Salahuddin, Ahmad (CGIAR Initiative on Asian Mega-Deltas, 2024)
Spatial data, also known as geospatial data, refers to any data that is directly or indirectly related to or contain information about a specific location on the Earth’s surface. The data represents earth features in its geographic position which plays important role in different sectors providing information of that specific location. The location specific data is crucial in decision making process since the information derived from the data provides essential context and insights of the real world. Spatial data, prepared in a standard process and organizedhelps decision-makers, scientists and other stakeholders understand patterns, trends, and relationships in geographical information, leading to more informative and effective decisions. Spatial data is visualized in maps to make it acceptable and readable to the stakeholders.